The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19042098
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Nature Restorativeness, Stress Level, and Nature Connectedness in the Association between Nature Exposure and Quality of Life

Abstract: This study aimed to test the mediating effects of nature restorativeness, stress, and nature connectedness in the association between nature exposure and quality of life (QoL). Urban and rural Lithuanian inhabitants (n = 924; 73.6% were women), mean age of 40.0 ± 12.4 years (age range of 18–79) participated in the study. In total, 31% of the respondents lived in rural areas. Study participants completed an online survey form with measures on sociodemographic factors, nature proximity, nature exposure, nature c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…A study on 863 participants in China investigated the links between nature exposure, nature connectedness, and mental wellbeing ( 73 ) and found that nature connectedness moderated the associations between nature exposure, as measured by visitation frequency, nearby greenspace and park quantity, and mental wellbeing. Similarly, another recent study revealed that nature connectedness and nature restorativeness mediated the relationship between nature exposure and quality of life in 924 Lithuanians ( 74 ). The increase in nature connectedness over the control group and baseline following a virtual nature experience is consistent with the well-established evidence of how nature exposure affects mental wellbeing by eliciting nature connectedness.…”
Section: Discussionmentioning
confidence: 83%
“…A study on 863 participants in China investigated the links between nature exposure, nature connectedness, and mental wellbeing ( 73 ) and found that nature connectedness moderated the associations between nature exposure, as measured by visitation frequency, nearby greenspace and park quantity, and mental wellbeing. Similarly, another recent study revealed that nature connectedness and nature restorativeness mediated the relationship between nature exposure and quality of life in 924 Lithuanians ( 74 ). The increase in nature connectedness over the control group and baseline following a virtual nature experience is consistent with the well-established evidence of how nature exposure affects mental wellbeing by eliciting nature connectedness.…”
Section: Discussionmentioning
confidence: 83%
“…It found that connection to nature moderated the associations between nature exposure, as measured by the frequency of visitation, amount of nearby green space and parks and mental well-being. Similarly, another recent study found that connection with nature mediated the link between nature exposure and quality of life (Baceviciene and Jankauskiene 2022).…”
Section: The Role Of Nature Relatednessmentioning
confidence: 80%
“…However, the social context of the place where the research population resides is of key importance, since the perception of quality of life is influenced by health, socio-political factors, and the degree of economic development of each country, and the difference between urban and rural environments differs depending on this context [ 40 , 41 ]. Regarding physical health, studies that apply this tool to explore the differences between rural and urban environments do not find significant differences, although it is expected that the rural environment will obtain better results because of the presence of green environments with restorative properties [ 42 ]. However, further research is required in this area to establish relationships.…”
Section: Discussionmentioning
confidence: 99%